Music education in the hospital: The improvising teacher - Bastos , Rossana Flores; Hettwer , Ana Lúcia de Marques e Louro (Seven Editora, 2023)
The music educator has a wide possibility of acting in different realities, from basic education schools to private music education, as well as social projects and environments that care for health, such as hospitals. Due to this wide demand for teaching and learning spaces, the teacher must have the possibility to experience different fields during training. In addition, studies are based on the human relationship that is interested in music has with the resource that stimulates the stimulus, through the search for a resource that can assist in health care. Based on practical experience in the hospital context and the writing of class diaries, analyzed according to Zabalza (2004), this excerpt from research carried out to understand the contributions of this practice to the training of music teachers, shows how the music educator becomes an improvising teacher in the hospital context. The analysis showed that these experiences of improvising on the constructed planning contribute to broadening the teacher's view of their practice and their students in any teaching context, contributing to the construction of a more humanized and integrative education. DOI:https://doi.org/10.56238/alookdevelopv1-127